Impact of Jilin Province Stroke Emergency Maps on Acute Stroke Care Improvement in Northeast China - Jin, Hang; Qu, Yang; Guo, Zhen-Ni; Yan, Xiu-Li; Sun, Xin; Yang, Yi (Frontiers in Neurology, 2020)
Objectives: Stroke burden is especially heavy in northeast China. Facilities with the capacity to perform acute reperfusion therapies for stroke are unevenly dispersed and are especially inadequate in rural areas. The aim of this study was to establish an effective measure to improve stroke emergency care, eventually increasing the capacity for reperfusion therapy in Jilin province, a less developed province in northeast China. Methods: We created the Jilin province Stroke Emergency Maps (JSEM), a regional stroke emergency network. Qualified hospitals in Jilin province were integrated into JSEM according to strict inclusion criteria. With constant evaluation and screening, more qualified hospitals may be enrolled into the JSEM, which is updated and published once per year. Locations of hospitals with the capacity to perform intravenous thrombolysis and emergency mechanical thrombectomy were labeled on the map. Results: After strict evaluation and screening, 19 designated hospitals were integrated into the JSEM in August 2017 (baseline). Following the implementation of the JSEM, 21 more designated hospitals (40 in all) were included in 2018, and 48 more designated hospitals were included in 2019. With the guidance of the JSEM, the rate of intravenous thrombolysis in Jilin province increased remarkably from 3.3% (2017, baseline) and 4.6% (2018) to 5.5% (2019). Mean door-to-needle time decreased from 62 minutes at baseline (2017) to 45 minutes 2 years later. The number of mechanical thrombectomy was increased from 457 at baseline (2017) to 749 (2018) and 1137 (2019) per year, respectively, and mean door-to-puncture time was shortened from 136 minutes to 120 minutes. Conclusion: The JSEM, a regional stroke emergency network, serves to improve patient care for stroke. The map’s publication increased rates of intravenous thrombolysis and mechanical thrombectomy. JSEM effectively connected more qualified designated hospitals, stroke patients and emergency medical service systems in Jilin province.